Perancangan Sistem Pengamanan Sepeda Motor Berbasis Kontrol Telegram - Cahyo Nugroho, Nur; Rhemadanu, Andreas; Aryo Putra Prayoga, Ferdianto; Pramono (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Motorcycles are very popular in Indonesia, with the number reaching 125,305,332 units in 2022 according to the Central Statistics Agency (BPS). However, this popularity also increases the risk of theft, which rose from 106 cases in 2021 to 183 cases in 2022 according to BAPPEDA Jogja. To address this issue, this study proposes a motorcycle security system controlled via Telegram. This system uses WiFi technology, allowing users to monitor and control their motorcycles remotely. The prototype employs an Arduino Uno microcontroller, an ESP8266 module for WiFi connectivity, vibration and PIR sensors to detect suspicious activity, and relays to activate alarms and cut off power to the motorcycle. The development method used is prototyping, which involves iterative feedback and refinement. The resulting design effectively reduces the risk of theft by providing early detection and quick response capabilities, thereby enhancing motorcycle security.